Doloto: Code Splitting for Network-Bound Web 2.0 Applications - Kiciman, Emre; Livshits, Ben (2007)
Modern Web 2.0 applications, such as GMail, Live Maps, Facebook and many others, use a combination of Dynamic HTML, JavaScript and other Web browser technologies commonly referred as AJAX to push page generation and content manipulation to the client web browser. This approach improves the responsiveness of these network-bound applications, but the shift of application execution from a back-end server to the client also often dramatically increases the amount of code that must first be downloaded to the browser. This creates an unfortunate Catch-22: to create responsive distributed Web 2.0 applications developers move code to the client, but for an application to be responsive, the code must first be transferred there, which takes time. In this paper, we present DOLOTO, a system that analyzes application workloads and automatically performs code splitting of existing large Web 2.0 applications. After being processed by DOLOTO, an application will initially transfer only the portion of code necessary for application initialization. The rest of the application’s code is replaced by short stubs—their actual function code is transfered lazily in the background or, at the latest, on-demand on first execution. Since code download is interleaved with application execution, users can start interacting with the Web application much sooner, without waiting for the code that implements extra, unused features. To demonstrate the effectiveness of DOLOTO in practice, we have performed experiments on five large widely-used Web 2.0 applications. DOLOTO reduces the size of initial application code download by hundreds of kilobytes or as much as 50% of the original download size. The time to download and begin interacting with large applications is reduced by 20-40% depending on the application and wide-area network conditions.